Natural Hazards and Peoples in the Indian Ocean World
XV, 318 p. 27 illus., 25 illus. in color.
Keywords: This book examines the dangers and the patterns of adaptation that emerge through exposure to risk on a daily basis. By addressing the influence of environmental factors in Indian Ocean World history, the collection reaches across the boundaries of the natural and social sciences, presenting case-studies that deal with a diverse range of natural hazards – fire in Madagascar, drought in India, cyclones and typhoons in Oman, Australia and the Philippines, climatic variability, storms and flood in Vietnam and the Philippines, and volcanic eruptions, earthquakes and tsunamis in Indonesia. These chapters, written by leading international historians, respond to a growing need to understand the ways in which natural hazards shape social, economic and political development of the Indian Ocean World, a region of the globe that is highly susceptible to the impacts of seismic activity, extreme weather, and climate change. .